What Does Vulnerability Mean? - Hoffmaster, Barry (The Hastings Center report, 2006)
Vulnerability does not mean much for our contemporary morality. It is antithetical to our emphasis on individualism and rationality; it requires that we attend to the body and to our feelings. Yet only by recognizing the depth and breadth of our vulnerability can we affirm our humanity.